PALEODEM/ What burned the forest? Wildfires, climate change and human activity during the Mesolithic – Neolithic transition in SE Iberian Peninsula - Sánchez-García, Carlos; Revelles, Jordi; Burjachs, Francesc; Euba, Itxaso; Expósito, Isabel; Ibáñez, J.; Schulte, Lothar.; Fernández-López de Pablo, Javier (Zenodo, 2022)
This repository contains new XRD data from the Villena paleolake, archaeological radiocarbon evidence from the Villena area and the R code used to produce Summed Probability distribution analyses. They correspond to the following reference: Sánchez-García, C., Revelles, J., Burjachs, F., Euba, I., Expósito, I., Ibáñez, J., Schulte, L., Fernández-López de Pablo, J.What burned the forest? Wildfires, climate change and human activity during the Mesolithic – Neolithic transition in SE Iberian Peninsula (submitted to Catena). We specify the content of file further down: Vinalopo.csv: the list of radiocarbon dates from Villena spanning ca.9500-5500 cal BP from the following sites: Arenal de la Virgen, Cueva del Lagrimal and Casa Corona. ngrip.csv: NGRIP GICC05 paleotemperature record based on oxygen isotope series from Rasmussen SO et al. 2006 A new Greenland ice core chronology for the last glacial termination. J. Geophys. Res. Atmos. 111 . (doi:10.1029/2005JD006079) andAndersen KK et al. 2006 The Greenland Ice Core Chronology 2005, 15–42ka.Part 1: constructing the time scale. Quat. Sci. Rev. 25, 3246–3257. Char.csv:Sedimentary charcoal data set from the Villena Paleolake (VL3 core) published by Jones, S.E., Burjachs, F., Fernández-López de Pablo (2018)DOI/10.5281/zenodo.1244003, according to the new Bacon chronological model of the Villena paleolake (Fernández-López de Pablo et al., 2022. Impacts of Early Holocene environmental dynamics on open-air occupation patterns in the Western Mediterranean: insights from El Arenal de la Virgen (Alicante, Spain). https://doi.org/10.31235/osf.io/5yqsr ) SPD_analysis.R: R script with the code to reproduce the SPD analysis presented in the manuscript. SupplMat1xlsl: an excel fileThis file is composed by 8 spreadsheets: ‘Selected variables 12.6-5.5’: all the data included in the time frame 12600-5500 cal BP, interpolated to 50 yr time windows. These data have been used for the Spearmans’rs correlation analysis (see spreadsheet ‘Spearmans’rs 12.6-5.5’ to track the results), ...